Measuring and comparing the (in)efficiency of German and Swiss hospitals - Lukas Steinmann; Gunnar Dittrich; Alexander Karmann; Peter Zweifel (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2003)
A nonparametric Data Envelopment Analysis (DEA) is performed on hospitals in the federal state of Saxony (Germany) and in Switzerland. This study is of interest from three points of view. First, contrary to most existing work, patient days are not treated as an output but as an input. Second, the usual DEA assumption of a homogeneous sample is tested and rejected for a large part of the observations. The proposed solution is to restrict DEA to comparable observations in the two countries. Finally, hospital beds are treated as a discretionary input in one DEA and as a fixed input in the other, and the effect on efficiency is related to differences in hospital planning in Germany and Switzerland. Based on the comparable observations, hospitals of Saxony have higher efficiency scores than their Swiss counterparts.
Keywords: I11; I18; C61; 330; International efficiency comparison; Hospitals; Data Envelopment Analysis; Krankenhaus; Technische Effizienz; Data-Envelopment-Analyse; Vergleich; Schätzung; Deutschland; Schweiz